Impact of World Trade Organization on Demand Pattern and Opportunities to Tea Farmers in Nepal - Sapkota, Keshav Bhakta (Tribhuvan University Journal, 2016)
Nepal became member of WTO after it adopted open market and economic liberalization policy. Obviously, this kind of membership tow TO could have some kind of implications on Nepalese market. This article is based on the empirical data generated through intensive fieldwork. This article reveals that after Nepal became member of WTO it has direct impact on the demand pattern of Nepalese market. But there is no influence in the creation of new employment opportunities. However, farmers have got different opportunities of getting trainings and access to formal and informal education. More importantly, access to WTO has transformed tea farming from subsistence to commercial and thus increasing the demand of Nepalese tea in international market.